The Relationship between Cognitive Disorders and Hippocampal Angle in Patients Multiple Sclerosis - Azin Shayganfar (مجله دانشکده پزشکی اصفهان, 2019)
Background: Multiple sclerosis (MS) is the most prevalent inflammatory demyelinating disease that involves central nervous system. Cognitive disorders are common complaint of patients with MS. Hippocampus is a part of brain that plays significant role in cognition, and is highly sensitive to inflammatory changes induced by MS. This study was the first study conducted to assess hippocampal angle in cognitive disorders occur in patients with MS.